The canopic equipment of the kings of Egypt - Dodson, Aidan 1962- (Kegan Paul, 1994)
While some containers were simple stone jars, many were objects of great artistic attainment, the high point perhaps being reached with the solid gold coffinettes of Tutankhamun and the gilded shrine that sheltered them, adorned by the exquisite figures of the four guardian goddesses. Such royal canopics are also of some historical import, one set of jars being key evidence of the existence of a new pharaoh of the Third Intermediate Period
Keywords: Canopen; Canopes - Égypte; Farao's; Funérailles - Rites et cérémonies antiques; Pharaons - Tombeaux; Canopic jars -- Egypt; Funeral rites and ceremonies -- Egypt; Pharaohs -- Tombs; Kanopenkasten; Bestattung; Pharao; Ägypten -- Altertum